Evaluation of Beclin-1 and Atg5 genes expression levels in peripheral blood cells of patients with rheumatoid arthritis - Bahareh Kardideh; Mona Sadeghalvad; Zahra Samimi; Hamid Reza Mohammadi Motlagh; Mahdi Taghadosi (Fiyz̤, 2019)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, which primarily affects the joints. During RA development, T cells and other immune cells are recruited to the synovial tissue and promote RA. Autophagy is a process in which intracellular organelles and compounds are degraded. Autophagy as a regulator of cell homeostasis can affect immune cells activation and contribute in RA pathogenesis. The aim of this study was to evaluate the autophagy-related genes (Atgs) expression in two groups of RA patients and healthy subjects. Materials and Methods: Peripheral blood was obtained from three groups of donors including 20 patients with early RA, 20 undertreatment RA patients (with methotrexate, hydroxychloroquine and prednisolone therapy) and 20 age- and sex-matched healthy subjects. The expression of two autophagy-related genes was investigated by the real-time PCR technique. Results: The Beclin-1 expression showed a 3.41-fold increase in the patients with early RA compared to healthy subjects but in the under treatment patients it was 1.5 times higher than healthy persons (P<0.05). The Atg5 gene expression in the early RA patients increased by 2.4 times more than healthy subjects (P<0.05). Conclusion: The findings of this study show that in early RA patients, the increased expression of Atgs can promote RA pathogenesis. Also, findings suggest that the decreased autophagy can reduce RA severity.